USE OF THE ALVARADO SCORE IN SUSPECTED ACUTE APPENDICITIS - Janković, Tamara; Đorđević, Stefan (Halo 194 Scientific Journal of Emergency Medicine, 2026)
INTRODUCTION/OBJECTIVE Appendicitis is an inflammation of the appendix,with the appearance of symptoms in the first 24 hours.Clinically,it presents with pain in the abdomen,most often in the lower right quadrant,increased temperature,loss of appetite,nausea and vomiting.Due to the non-specificity of symptoms,scoring systems have been developed to facilitate diagnostic of suspected appendicitis.Objective is the use of the Alvarado score at the prehospital level in case of suspected acute appendicitis.CASE REPORT The Department of Emergency Medicine in Belgrade was sent a call for intervention due to abdominal pain.The periumbilical pain started last night,she had fever and nausea.Alvarado score was 6, the patient was transported to the ER where the diagnosis of acute appendicitis was confirmed.CONCLUSION Prehospital diagnostics of acute appendicitis is based on history and physical examination,where use of the Alvarado score can be very important,with the aim of reducing the risk of complications,morbidity and mortality.KEY WORDS alvarado, scabies, appendicitis, ripasa
Keywords: alvarado score appendicitis ripasa